The Effect of Nanocurcumin Administration on Plasma Malondialdehyde (MDA) Levels in Pregnant Wistar Rats (Rattus norvegicus) as a Preeclampsia Model: Pengaruh Pemberian Nano Kurkumin terhadap Kadar Malondialdehyde (MDA) Plasma Darah Pada Tikus Wistar (Rattus norvegicus) Bunting Model Preeklampsia - Subandi, Subandi; Sari, Laras Indah; Nurdiana, Nurdiana (Majalah Kesehatan Indonesia, 2025)
Preeclampsia is a pregnancy complication associated with oxidative stress and increased levels of malondialdehyde (MDA), leading to endothelial dysfunction and impaired placental perfusion. Nanocurcumin possesses antioxidant properties that can mitigate oxidative stress; however, its effectiveness in reducing MDA levels in preeclampsia requires further investigation. This study aims to evaluate the effect of nanocurcumin administration on plasma MDA levels in pregnant Rattus norvegicus models of preeclampsia induced using Nw-Nitro-L-Arginine Methyl Ester (L-NAME). A total of 24 pregnant Wistar rats were divided into six groups: negative control (K-), positive control (K+), and four treatment groups receiving nanocurcumin at doses of 25 mg/KgBW (P1), 50 mg/KgBW (P2), 100 mg/KgBW (P3), and 200 mg/KgBW (P4). Preeclampsia was induced by administering L-NAME (125 mg/KgBW) for six consecutive days, followed by nanocurcumin treatment. Plasma MDA levels were measured using the Thiobarbituric Acid (TBA) assay and analyzed using the Kruskal-Wallis test and post-hoc Mann-Whitney test (p < 0.05). Nanocurcumin administration at 25 mg/KgBW and 50 mg/KgBW significantly reduced MDA levels compared to the preeclampsia group without treatment (p = 0.042, p < 0.05). However, a high dose of 200 mg/KgBW increased MDA levels, indicating a potential pro-oxidant effect. Low to moderate doses of nanocurcumin effectively reduced MDA levels in the preeclampsia model, but further studies are necessary to determine the optimal dosage and its safety in humans. Abstrak: Preeklamsia merupakan komplikasi kehamilan yang berhubungan dengan stres oksidatif dan peningkatan kadar malondialdehyde (MDA), yang menyebabkan disfungsi endotel dan gangguan perfusi plasenta. Nanokurkumin memiliki sifat antioksidan yang dapat mengurangi stres oksidatif, tetapi efektivitasnya dalam menurunkan kadar MDA pada preeklamsia masih perlu dikaji lebih lanjut. Penelitian ini bertujuan untuk mengevaluasi pengaruh pemberian nanokurkumin terhadap kadar MDA plasma pada tikus putih (Rattus norvegicus) bunting model preeklamsia yang diinduksi menggunakan Nw-Nitro-L-Arginine Methyl Ester (L-NAME). Sebanyak 24 ekor tikus Wistar bunting dibagi menjadi enam kelompok: kontrol negatif (K-), kontrol positif (K+), serta empat kelompok perlakuan yang menerima nanokurkumin dengan dosis 25 mg/KgBW (P1), 50 mg/KgBW (P2), 100 mg/KgBW (P3), dan 200 mg/KgBW (P4). Induksi preeklamsia dilakukan dengan pemberian L-NAME (125 mg/KgBW) selama enam hari, diikuti pemberian nanokurkumin. Kadar MDA plasma diukur menggunakan metode Thiobarbituric Acid (TBA) assay dan dianalisis dengan uji Kruskal-Wallis dan post-hoc Mann-Whitney (p < 0.05). Pemberian nanokurkumin 25 mg/KgBW dan 50 mg/KgBW secara signifikan menurunkan kadar MDA dibandingkan kelompok preeklamsia tanpa terapi (p = 0.042, p < 0.05). Namun, dosis tinggi (200 mg/KgBW) justru meningkatkan kadar MDA, menunjukkan efek pro-oksidan. Nanokurkumin dosis rendah hingga sedang efektif dalam menurunkan kadar MDA pada model preeklamsia, tetapi studi lanjutan diperlukan untuk menentukan dosis optimal dan keamanannya pada manusia.